2022 ETA Consensus Statement: What are the indications for post-surgical radioiodine therapy in differentiated thyroid cancer?. Issue 1 (1st January 2022) - Pacini, Furio; Fuhrer, Dagmar; Elisei, Rossella; Handkiewicz-Junak, Daria; Leboulleux, Sophie; Luster, Markus; Schlumberger, Martin; Smit, Johannes W
Abstract : Modern use of post-operative radioactive iodine (RAI) treatment for differentiated thyroid cancer (DTC) should be implemented in line with patients' risk stratification. Although beneficial effects of radioiodine are undisputed in high-risk patients, controversy remains in intermediate-risk and some low-risk patients. Since the last consensus on post-surgical use of RAI in DTC patients, new retrospective data and results of prospective randomized trials have been published, which have allowed the development of a new European Thyroid Association (ETA) statement for the indications of post-surgical RAI therapy in DTC. Questions about which patients are candidates for RAI therapy, which activities of RAI can be used, and which modalities of pre-treatment patient preparation should be used are addressed in the present guidelines.